ANALISIS POLA TABUHAN BERUAS PADA MUSIK IRINGAN TARI JEPIN LANGKAH BISMILLAH DI KELURAHAN SIANTAN HILIR KECAMATAN PONTIANAK UTARA - Rahayu Rahayu; Yudhistira Oscar Olendo; Asfar Muniir (Universitas Tanjungpura, 2021)
AbstractThe background of this research is to analyze the beruas wasp pattern of the jepin dance accompaniment of bismillah steps. There is a peculiarity in the wasp pattern. The problems in this research are how is Beruas playing technique, and how the analysis of the Beruas beating patterns on the accompaniment of Jepin Langkah Bismillah dance. The method in this research is the descriptive method in the form of qualitative research. The approach used is the musicology approach. The source of data in the study were sources. The data in this research are the results of interview, observations, documentation results and a diary book regarding the Analysis of Beruas Beating Patterns on the accompaniment of Jepin Langkah Dance. Techniques of data collection in this research are observation, interview, and documentation. The validity test of the data in this research is through the extension of observations and triangulation. The technique of data analysis in this research is done qualitatifvely. The result of this research is there are four Beruas beating patterns on the accompaniment of jepin langkah bismillah dance, which consist of the opening beating pattern, the lampas beating pattern, the sitting takhto beating pattern, and the standing takhto beating pattern.Keywords: Beating Pattern, Beruas, The Accompaniment of Jepin Langkah Bismillah.